Distraction and Placebo - Buhle, Jason T.; Stevens, Bradford L.; Friedman, Jonathan J.; Wager, Tor D. (Psychological Science, 2012)
An explosion of recent research has studied whether placebo treatments influence health-related outcomes and their biological markers, but almost no research has examined the psychological processes required for placebo effects to occur. This study tested whether placebo treatment and cognitive distraction reduce pain through shared or independent processes. We tested the joint effects of performance of an executive working memory task and placebo treatment on thermal pain perception. An interactive effect of these two manipulations would constitute evidence for shared mechanisms, whereas additive effects would imply separate mechanisms. Participants ( N = 33) reported reduced pain both when they performed the working memory task and when they received the placebo treatment, but the reductions were additive, a result indicating that the executive demands of the working memory task did not interfere with placebo analgesia. Furthermore, placebo analgesia did not impair task performance. Together, these data suggest that placebo analgesia does not depend on active redirection of attention and that expectancy and distraction can be combined to maximize pain relief.